Heart rate recovery is blunted in soccer athletes during a competitive season - dos Santos Corrêa, A. P.; Nazario Viecili, P. R.; Callegaro, C. C. (Journal of Sports Medicine & Doping Studies, 2015)
Since vagal control of the heart rate (HR) is impaired in athletes during the competition period, we hypothesized that soccer athletes engaged in a competitive season would exhibit an impaired HR recovery after exercise. Seven male soccer athletes and 9 male sedentary individuals were matched for age. Heart rate variability (HRV) was assessed in sitting and upright position for 10 min. The HR and blood pressure (BP) were measured at rest, during treadmill exercise test and recovery period. Individuals were 24 ± 3 years old. The athletes had a lower HR (55 ± 3 bpm vs. 72 ± 10 bpm; P< 0.001) and systolic BP (108 ± 4 mmHg vs. 118 mmHg ± 6; P< 0.001) than sedentary individuals at rest. Low frequency (LF) and high frequency (HF) component of the HR were similar in both groups at sitting position. Active orthostatic test increased LF and reduced HF in both groups. Soccer athletes showed a higher maximal oxygen consumption (63 ± 5 ml.kg-1.min-1 vs. 47 ± 5 ml/kg.min; P= 0.001). The HRV in the first minute after exercise was similar in both groups. High-intensity exercise performed at the competition season may blunt heart rate recovery in soccer athletes. (Abstract)